CircERBB2IP promotes post-infarction revascularization via the miR-145a-5p/Smad5 axis - Xianping Long; Zhimei Qiu; Chaofu Li; Yan Wang; Jiao Li; Ranzun Zhao; Jidong Rong; Ning Gu; Jinson Yuan; Junbo Ge; Bei Shi (Elsevier, 2022)
Myocardial infarction is one of the leading diseases causing death and disability worldwide, and the revascularization of damaged tissues is essential for myocardial-injury repair. Circular RNAs (circRNAs) are widely involved in physiological and pathological processes in various systems throughout the body, and the role of circRNAs in cardiovascular disease is gaining attention. In this study, we determined that circERBB2IP is highly expressed in the hearts of newborn mice. Silencing or overexpression of circERBB2IP inhibited and promoted angiogenesis in vivo and in vitro, respectively. Mechanistically, the transcription factor GATA4 promotes the production of circERBB2IP. Furthermore, circERBB2IP functioned as an endogenous miR-145a-5p sponge and was able to sequester and repress miR-145a-5p activity, which led to an increased expression level of Smad5. In summary, circERBB2IP can promote angiogenesis after myocardial infarction through the miR-145a-5p/Smad5 axis. These data suggest that circERBB2IP may be a potential therapeutic target for the treatment of myocardial infarction.